PENGARUH LOAN TO DEPOSIT RATIO (LDR), DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSETS (ROA) TERHADAP HARGA SAHAM PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BEI TAHUN 2015-2019 - Ika Wahyuni; Triska Dewi Pramitasari (Growth, 2021)
Debt to Equity Ratio (DER) and Return on Assets (RoA) partially on the stock price variable at Conventional Commercial Banks (2) to determine the effect of the variable Loan Deposit Ratio (LDR), Debt to Equity Ratio (DER) and Return on Assets (RoA) simultaneously on the stock price variable at Conventional Commercial Banks (3) to determine the Loan to Deposit Ratio (LDR) variable, Debt to Equity Ratio (DER) ) and Return on Assets (RoA) are dominant to the variable of stock prices at Conventional Commercial Banks. Methods of data analysis used in this research are classical assumption test, multiple linear regression, t test, F test, dominant test and coefficient of determination. The results of multiple linear regression analysis are Y = 67,534,048 – 607,852 X1 – 19,820X2 + 1,673,280 X3 + e. Partially, LDR has a significant effect with tcount -4.018 < ttable -2.028, DER has a significant effect with tcount -3.180 < ttable -2.028 and RoA has no significant effect with tcount 1.546 < ttable 2.028. Simultaneously LDR, DER and RoA have a significant effect with Fcount 19.833 > Ftable 2.87. The most dominant variable in this study is LDR with a value of -4.018